The mode of antimicrobial action of Cinnamomum burmannii’s essential oil & cinnamaldehyde - Darnis, Deny Susanti; Awang, Anis Fadhlina Izyani; Bakhtiar, M. Taher (2015)
The incidence of antibiotic resistance and its side effect have urged scientist to search for new antimicrobial substances. Cinnamons are rich in essential oils which mainly consist of cinnamaldehyde as its bioactive compounds. The present study was designed to postulate the mode of antimicrobial actions of both essential oil and cinnamaldehyde against E. coli, S. aureus and C. albicans. The essential oil was extracted by steam distillation. Column chromatography was carried out in order to isolate cinnamaldehyde from the essential oil. Spectroscopic technique was used to characterize the isolated compound, cinnamaldehyde. There were four modes of action tested which included time-killing assay, salt tolerance assay, crystal violet assay and leakage of cellular metabolites. All of the tests were done in triplicate. The antimicrobial effect on the cell membrane was dose-dependent whereby stronger antimicrobial action was observed by cinnamaldehyde at concentration equal to 4×MIC (1.33 mg/mL) as compared to the essential oil. The potential of cinnamaldehyde as a potent antimicrobial compound of the cinnamon essential oil was discovered and proven to act on the cell membrane of microorganisms tested particularly against C. albicans.